simplifying
5(x + -6) = 2(x + 3)
reorder the terms:
5(-6 + x) = 2(x + 3)
(-6 * 5 + x * 5) = 2(x + 3)
(-30 + 5x) = 2(x + 3)
reorder the terms:
-30 + 5x = 2(3 + x)
-30 + 5x = (3 * 2 + x * 2)
-30 + 5x = (6 + 2x)
solving
-30 + 5x = 6 + 2x
solving for variable 'x'.
move all terms containing x to the left, all other terms to the right.
add '-2x' to each side of the equation.
-30 + 5x + -2x = 6 + 2x + -2x
combine like terms: 5x + -2x = 3x
-30 + 3x = 6 + 2x + -2x
combine like terms: 2x + -2x = 0
-30 + 3x = 6 + 0
-30 + 3x = 6
add '30' to each side of the equation.
-30 + 30 + 3x = 6 + 30
combine like terms: -30 + 30 = 0
0 + 3x = 6 + 30
3x = 6 + 30
combine like terms: 6 + 30 = 36
3x = 36
divide each side by '3'.
x = 12
simplifying
x = 12
this should .